All-solid-state' electrochemistry of a protein-confined polymer electrolyte film - Parthasarathy, Meera; Pillai, Vijayamohanan K.; Mulla, Imtiaz S.; Shabab, Mohammed; Khan, Mohammad Islam (Biochemical and Biophysical Research Communications, 2007)
Interfacial redox behavior of a heme protein (hemoglobin) confined in a solid polymer electrolyte membrane, Nafion (a perfluoro sulfonic acid ionomer) is investigated using a unique `all-solid-state' electrochemical methodology. The supple phase-separated structure of the polymer electrolyte membrane, with hydrophilic pools containing solvated protons and water molecules, is found to preserve the incorporated protein in its active form even in the solid-state, using UV-visible, Fluorescence (of Tryptophan and Tyrosine residues) and DRIFT (diffuse reflectance infrared Fourier transform) spectroscopy. More specifically, solid-state cyclic voltammetry and electrochemical impedance of the protein-incorporated polymer films reveal that the Fe2+-form of the entrapped protein is found to bind molecular oxygen more strongly than the native protein. In the `all-solid-state' methodology, as there is no need to dip the protein-modified electrode in a liquid electrolyte (like the conventional electrochemical methods), it offers an easier means to study a number of proteins in a variety of polymer matrices (even biomimetic assemblies). In addition, the results of the present investigation could find interesting application in a variety of research disciplines, in addition to its fundamental scientific interest, including protein biotechnology, pharmaceutical and biomimetic chemistry. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: all-solid-state; cyclic voltammetry; hemoglobin; Impedance; Nafion; redox behavior

Acetone vapour sensing characteristics of undoped and Zn, Ce doped SnO2 thick film gas sensor - Bagal, L. K.; Patil, J. Y.; Bagal, K. N.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Materials Research Innovations, 2013)
The nanocrystalline materials of zinc and ceria doped tin oxide [(Zn+Ce)-SnO2] powders were synthesised by coprecipitation method and investigated for their sensing properties towards liquid petroleum gas (LPG), ethanol, ammonia and acetone vapour. The crystal structure and phase of the as synthesised and sintered powders were characterised by X-ray diffractometer and the microstructure by scanning electron microscopy. All the doped and undoped SnO2 compositions revealed single phase solid solution formation. Transmission electron microscope results indicated that well crystallised (Zn+Ce) doped SnO2 particles of size similar to 7 nm were obtained at the annealing temperature of 650 degrees C. The reduction in grain size of the metal oxide is a key factor to enhance the gas sensing properties. The doping of zinc, ceria in SnO2 has reduced the grain size and improved the gas response. The results of gas sensing measurements showed that the thick films deposited on alumina substrates using screen printing technique exhibited high response to acetone at an operating temperature of 300 degrees C. Further, the selectivity of the sensor towards acetone with respect to other reducing gases (LPG, ethanol and ammonia) was studied.
Keywords: Gas; Screen printing; Sensor; SnO2